Unmasking autism: gender differences in diagnostic practices and challenges in Norway’s mental healthcare services for children and youth - Katrine Lyngvær Fredriksen; Katrine Lyngvær Fredriksen; Alexander G. Page; Celina Lindhardt; Celina Lindhardt; Sobh Chahboun (Frontiers in Education)
Gender plays a critical role in the recognition, diagnosis, and support of children with Autism Spectrum Disorder (ASD). This qualitative study explores the perspectives of special education professionals, who are involved in both diagnosing and following up children with Autism, on how ASD manifests in girls and the diagnostic challenges that arise. Although boys are more frequently diagnosed—and often at younger ages—emerging research and clinical experience suggest that girls may exhibit more nuanced and socially adaptive traits that fall outside traditional diagnostic expectations. Girls with ASD often use compensatory behaviors such as social mimicry, masking of difficulties, and scripting in social situations to conform to neurotypical norms. This study is based on semi structured interviews with three special educators from the Child and Adolescent Psychiatric Services. While these strategies can temporarily obscure core challenges in communication and social reciprocity, they frequently contribute to delayed identification and are associated with long-term psychological consequences, including fatigue, anxiety, and depression. Participants noted that girls are typically referred for evaluation later in adolescence, often in connection with internalizing symptoms such as eating disorders or mood-related concerns, rather than overt behavioral issues. Findings highlight the limitations of diagnostic frameworks that are largely based on male-typical presentations of ASD and emphasize the need for gender-informed assessment practices. This study underscores the importance of developing diagnostic tools and support strategies that account for the diverse ways ASD may present in girls, thereby enhancing early identification, reducing misdiagnosis, and promoting more equitable support within education and mental health services.